Analysis of the Effect of Third Party Funds (DPK), Net Interest Margin (NIM), Non Performing Loans (NPL) on Total Loans in an Effort to Improve Bank Performance at PT. Central Kalimantan Bank - Radot Angga Sitorus (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
The purpose of this study is to analyze the effect of third party funds (DPK), Net Interest Margin (NIM) and Non-Performing Loans (NPL) on total loans partially or simultaneously. This type of research is quantitative research using multiple linear regression analysis tools, the results of this study indicate that simultaneously third party funds, net interest margin and non-performing loans affect the total credit of PT. Central Kalimantan Bank. Partially, third party funds and non-performing loans have a significant effect on total credit. Meanwhile, net interest margin has no significant effect on total credit